MODERNIZATION OF JAPAN (Heritage, 2021)
The aim of this paper is to examine socio-economic factors, both in Japan itself and at the world political scene, which influenced the creation of an authentic path to modernization, with special reference to the specific circumstances which lead to its successful completion. Modernization of Japan is primarily related to the Meiji period, which was a milestone in Japanese history and a complete turning point from the previous policy and state system. Reforms were carried out in all fields. The goals of these reforms were adaptation and modernization, resembling successful and developed countries of the West. This paper presents the path of Japan from an isolated country to an equal member of the international community, while maintaining its national and cultural identity.In mid-19th century, Japan was closed to the Western world and its technology was progressing very slowly. Shortly after, a sharp turn was made with the Meiji reform and the know-how from the West that was accepted in the country. Before that period, Japan was self-isolated precisely in the period of epochal scientific, cultural and artistic achievements of Western Europe. Due to these circumstances, such a rapid change in the social and political system is even more surprising.As a result of the reforms, Japan became a country that successfully withstood the most challenging period in its hitherto history, protecting traditional culture in the process of accelerated modernization. In just a few decades, Japan succeeded in what no one had done ever before – it turned a self-isolated feudal state into a social and state system with an excellent basis for a continuous development according to Western models, while maintaining its national identity.
Keywords: Meiji Reform, Japan, Wakon Yosai, Education, Ekonomic Modernization